Description Of Keyword Analysis: A Bibliometric Study Of Interpersonal Communication - Darmawati Darmawati (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2022)
The aim of this study was to assess the most relevant themes related to interpersonal communication by bibliometric analysis using the keyword "interpersonal communication" as input to gain a full understanding of interpersonal communication and understand the current research concentration. The research method used is literature review by collecting data through the Publish of Perish application because it is considered the best choice for bibliometric analysis. As a bibliometric analysis tool for visualizing a network of authors, quotes and keywords, the VOSviewer software results show that Every year, there are more and more papers on interpersonal communication, a trend indicating increasing interest in the subject. A Purwanto is the author with the most citations overall. Bibliometric analysis offers relevant details on the main researched issues of interpersonal communication.